IDENTIFICATION OF POTENTIAL DONORS THROUGH GENE PROFILING FOR RICE IMPROVEMENT - and V. GOURI SHANKAR, D. DEV KUMAR, D. VISHNU VARDHAN REDDY, P. RAGHUVEER RAO, M. SHESHU MADHAV (The Journal of Research, PJTSAU, 2019)
The experimental field was laid in RBD design replicated thrice using 30 advanced breeding lines and BPT-5204 as quality check. For characterization of advanced breeding lines seven genes (Gn1, Gn2, SCM2, SCM3, Gs3, Gw5, Spl14) and three QTLs (Yld12.1, Yld2.1 and Yld2.1) for grain yield; two genes (Gn1 and Gn2) for grain number; two genes (SCM2 and SCM3) for strong culm; one gene each for grain weight (Gw5); grain size (Gs3), filled grains per panicle (Spl14) were selected. Upon genotyping, only one advanced breeding line SP-08 showed the presence of the seven yield contributing genes/QTLs indicatingpossibility of higher yield potential. Two advanced breeding lines showed the presence of six yield contributing genes/QTLs. They are SP-69 contain (Gn1, Gn2, SCM3, Gw5, Spl14, Yld2.1) and SP-70 contain genes/QTLs (Gn1, SCM3, Gw5, Gs3, Yld2.1, Yld12.1). Whereas four advanced breeding lines showed the presence of five yield contributing genes. They are SP-37 (Gn2, SCM3, Gw5, Yld12.1, Yld2.1), SP-55 (Gn2, SCM2, SCM3, Gw5, Yld2.1), SP-75 (Gn1, Gn2, SCM3, Gw5, Yld12.1) andSP-61 (Gn1, Gn2, SCM2, Gw5, Yld 2.1).